Towards a more rapid diagnosis of rapidly progressive glomerulonephritis. Issue 6747 (11th August 1990) - Cassidy, M J; Gaskin, G; Savill, J; Pusey, C D; Rees, A J
Abstract : An attempt was made to provide simple practical guidelines to alert general practitioners to the diagnosis of rapidly progressive glomerulonephritis and lead to early referral to hospital. The duration of illness before referral to this hospital and its effect on outcome in patients with crescentic nephritis were assessed retrospectively from the case notes of 24 patients referred over two years. Four patients had Goodpasture's syndrome, 11 Wegener's granulomatosis, seven microscopic polyarteritis, and two idiopathic progressive glomerulonephritis. The duration of symptoms before referral to the local hospital was similar in the four groups of patients and varied from one week to 28 months (mean 10 months). The duration of stay in the local hospital was two, nine, 11, and 180 days in the patients with Goodpasture's syndrome and a mean of four days (range one to eight) in those with Wegener's granulomatosis and 10 days (one to 18 days) in those with microscopic polyarteritis. In the local hospital the diagnosis was based on the results of renal biopsy and detection of antibodies to glomerular basement membrane in two patients with Goodpasture's syndrome and on the results of renal biopsy in seven of the other patients aided by the detection of antibodies to the cytoplasm of neutrophils (ANCA) in 10. Three of the 24 patients died and four required maintenance haemodialysis. Patients who present to their general practitioners with persistent non-specific symptoms should have a urine dipstick test and then blood tests and emergency referral to hospital if necessary. Hospital physicians should be aware of the speed and accuracy with which current assays can confirm a diagnosis of rapidly progressive glomerulonephritis.